2018
DOI: 10.1038/s41598-018-22319-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Features Differentiate Between Normal and Tumoral High-Fdg Uptake

Abstract: Identification of FDGavid- neoplasms may be obscured by high-uptake normal tissues, thus limiting inferences about the natural history of disease. We introduce a FDG-PET radiomics tissue classifier for differentiating FDGavid- normal tissues from tumor. Thirty-three scans from 15 patients with Hodgkin lymphoma and 68 scans from 23 patients with Ewing sarcoma treated on two prospective clinical trials were retrospectively analyzed. Disease volumes were manually segmented on FDG-PET and CT scans. Brain, heart, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…A previous study showed that statistical RMS was able to predict pathological response after chemoradiation in non-small cell lung cancer (NSCLC), by identifying gross residual response 35 . Statistical RMS combined with other intensity statistical features was able to distinguish bladder tumor tissue from other normal tissues in fluorodeoxyglucose-positron emission tomography (FDG-PET) scan 36 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that statistical RMS was able to predict pathological response after chemoradiation in non-small cell lung cancer (NSCLC), by identifying gross residual response 35 . Statistical RMS combined with other intensity statistical features was able to distinguish bladder tumor tissue from other normal tissues in fluorodeoxyglucose-positron emission tomography (FDG-PET) scan 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The study indicated that PET/MR was more efficient in characterization and visualization and showed high lesion detection and good image quality of NPC compared with PET/CT. Some studies have shown that the combination of PET and MRI images and the comprehensive analysis of the molecular metabolism and microstructure characteristics of the tumors are of great value in the differential diagnosis and prognosis analysis of tumors (5,6). However, there are relatively few PET/MR studies on the staging of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…The automatic heart classification is challenging [ 23 ] due to the variable uptake behavior. In half of our patients with misclassified heart volumes an untypical cardiac uptake pattern was seen.…”
Section: Discussionmentioning
confidence: 99%
“…This sensitive threshold [ 24 , 25 ] was chosen to include all potential tumor lesions in our evaluation. Different segmentation thresholds were used by other authors: fixed thresholds of an SUV of 2.5 [ 12 , 16 ], 3.0 [ 23 ] or 4.0 [ 26 ], or adaptive thresholds of 41%/42% of the SUVmax [ 11 , 16 , 26 , 27 ] or background-related thresholds [ 12 , 16 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation